2022
DOI: 10.1002/ejoc.202200014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure Confirmation of Selagibenzophenone C

Abstract: We report the first total synthesis of natural diarylbenzophenone selagibenzophenone C recently isolated from a plant species Selaginella tamariscina, traditionally used in folklore medicines. The framework of the natural compound is assembled via Suzuki‐Miyaura cross‐coupling and the addition of organometallic species. Following some ambiguities in the assignment of the structures for some of the natural products belonging to this compound class, the spectral data reported for the isolated selagibenzophenone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This alcohol was prepared in two steps from 2,4-dichlorobenzaldehyde ( 13) by Suzuki cross-coupling with 4-methoxyphenyl boronic acids to yield aldehyde 14 and the addition of 4-methoxyphenylmagnesium bromide (15). Such alcohol contains the framework of another representative of the selaginellacea polyphenols, namely selagibenzophenone C. [9,14] The treatment of alcohol 16 with an excess of boron tribromide provided corresponding arylated fluorene 17 in 70 % yield.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This alcohol was prepared in two steps from 2,4-dichlorobenzaldehyde ( 13) by Suzuki cross-coupling with 4-methoxyphenyl boronic acids to yield aldehyde 14 and the addition of 4-methoxyphenylmagnesium bromide (15). Such alcohol contains the framework of another representative of the selaginellacea polyphenols, namely selagibenzophenone C. [9,14] The treatment of alcohol 16 with an excess of boron tribromide provided corresponding arylated fluorene 17 in 70 % yield.…”
Section: Synthesismentioning
confidence: 99%
“…The structural curiosity and the biological activity of these metabolites attracted the attention of synthetic as well as medicinal chemists. We reported a formal synthesis of selaginpulvilins C and D, [12] as well as selagibenzophenones A–C, [13,14] and clarified structural ambiguities, related to selagibenzophenone B. We also developed several derivatives of selagibenzophenone A ( 5 ) and identified a compound with selective cytotoxicity toward the prostate cancer cell lines, with negligible toxicity toward the healthy cells [15] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Chen et al reported the isolation of selagibenzophenone C. [21] The reported therapeutic potential of Selaginella-derived plant products as well as their structural peculiarity sparked interest in the synthesis of these natural products and derivatives thereof. We have recently become interested in the chemistry of Selaginella constituents and reported the formal total synthesis of selaginpulvilins C and D. [22] Furthermore, we prepared selagibenzophenones A (4 aa), B (3), [23] and C [24] and demonstrated that the structure of selagibenzophenone B was incorrectly elucidated. The compound reported as selagibenzophenone B (3) [19] (or selaphenin A [20] ) was, in fact, selagibenzophenone A (4 aa).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently become interested in the chemistry of Selaginella constituents and reported the formal total synthesis of selaginpulvilins C and D [22] . Furthermore, we prepared selagibenzophenones A ( 4 aa ), B ( 3 ), [23] and C [24] and demonstrated that the structure of selagibenzophenone B was incorrectly elucidated. The compound reported as selagibenzophenone B ( 3 ) [19] (or selaphenin A [20] ) was, in fact, selagibenzophenone A ( 4 aa ) [23] …”
Section: Introductionmentioning
confidence: 99%